Perspectives of public health organizations partnering with refugee, immigrant, and migrant communities for comprehensive COVID-19 case investigation and contact tracing - Dawson-Hahn, Elizabeth; Fredkove, Windy; Karim, Sayyeda; Mohamed, Farah; Abudiab, Seja; de Acosta, Diego; Ebengho, Sabrina; Garcia, Yesenia; Hoffman, Sarah; Keaveney, Megan; Mann, Erin; Thomas, Christine; et al. (Frontiers in Public Health, 2023)
Objectives To understand public health organizations’ experiences providing comprehensive COVID-19 case investigation and contact tracing, and related promising practices with refugee, immigrant and migrant communities. Methods We interviewed public health professionals (September 2020 to February 2021) from local and state health departments using a geographically stratified, purposive sampling approach. A multidisciplinary team at the National Resource Center for Refugees, Immigrants and Migrants (NRC-RIM) conducted a thematic analysis of the data. Results Six themes were identified: understanding community and public health context, cultivating relationships, ensuring linguistic and cultural concordance, communicating intentionally, evolving response, and implementing equity. The interconnection of themes and promising practices is explored. Conclusion As public health continues to learn from and build upon COVID-19 response experiences, the thematic findings and potential promising practices identified in this project may foster proactive, community-engaged solutions for public health, and other organizations working and partnering with refugee, immigrant, and migrant communities. Implementing these findings with COVID-19 into current and future public health crisis responses may improve public health, collaborations with refugee, immigrant, and migrant communities, and staff wellbeing.